A photocatalyst-free photo-induced denitroalkylation of β-nitrostyrenes with 4-alkyl substituted Hantzsch esters at room temperature. Issue 14 (2nd April 2020) - Zhang, Siyu; Li, Yaming; Wang, Jiaao; Hao, Xinyu; Jin, Kun; Zhang, Rong; Duan, Chunying
Graphical abstract: Highlights: β -Nitrostyrenes was denitroalkyled using 4-alkyl substituted Hantzsch esters at room temperature. The reaction can be conducted without photocatalyst. The di- t -butyl peroxide serves as a radical initiator under xenon lamp. Selective formation of E -isomer products. Abstract: A photocatalyst-free stereoselectively photo-induced strategy for the denitroalkylation of β -nitrostyrenes using 4-alkyl substituted Hantzsch esters as the alkyl source under xenon lamp irradiation is developed. The reaction proceeds at room temperature and affords the corresponding products in moderate to excellent yields. The oxidant di- t -butyl peroxide serves as an efficient radical initiator under irradiation of a Xenon lamp, initiating alkyl radicals from the 4-alkyl substituted Hantzsch esters.